Strategic Orientation of Mexican Family-owned Businesses and Its Influence on Corporate Social Responsibility Practices - Aguilar , José Luis Esparza; Maciel, Argentina Soto; Sánchez, José Luis Zapata; Hervert, María de Jesús Pérez (Organizations and Markets in Emerging Economies, 2020)
The aim of this article was to determine whether the strategic orientation of family-owned businesses influences Corporate Social Responsibility (CSR) practices. For this purpose, a questionnaire was administered to a sample of 245 family-owned businesses in the southern part of the southeastern Mexican state of Quintana Roo. Variables attributed to CSR measurements were environment, society, employees, and customers, as well as business-level strategies of prospector, analyzer, defender, and reactor as defined by Miles and Snow. Results showed that family-owned businesses with a strategic orientation as prospector and analyzer have higher development levels of CSR practices, reactor businesses demonstrated lower development levels of CSR practices. Prospector and analyzer businesses tend to be product developers and innovators in their respective markets.
Keywords: family-owned business; strategic orientation; CSR; micro-business; Mexico